2005
DOI: 10.1002/anie.200500522
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Ring Contraction En Route to the Chartelline Alkaloids

Abstract: One‐of‐a‐kind. A bromine‐induced rearrangement has been designed for the formation of the spiro‐β‐lactam ring present in the structurally unique chartelline alkaloids (see picture of chartelline A). This method is used in combination with others to provide rapid access to the carbocyclic skeletons of the chartelline, securine, and securamine alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Pleasingly, a-allenols 1 c and 1 d reacted with BH acetates 2 a and 2 b to furnish selectively the desired spiroazetidinones 6 a-d in moderate to good yields (Scheme 3). [8,9] When a-allenol 1 c and BH acetate containing nitrile 2 c were subjected to this Pd II -catalyzed protocol, the reaction did not yield the expected adduct 6 e, which would have arisen by S N 2 substitution by attack at the methylenic position remote from the leaving group, followed by migration of the double bond. Interestingly, under the present conditions the reaction exclusively led to the spiroazetidinone 7, probably by way of a regio-and diastereospecific S N 1 substitution (Scheme 4).…”
mentioning
confidence: 98%
“…Pleasingly, a-allenols 1 c and 1 d reacted with BH acetates 2 a and 2 b to furnish selectively the desired spiroazetidinones 6 a-d in moderate to good yields (Scheme 3). [8,9] When a-allenol 1 c and BH acetate containing nitrile 2 c were subjected to this Pd II -catalyzed protocol, the reaction did not yield the expected adduct 6 e, which would have arisen by S N 2 substitution by attack at the methylenic position remote from the leaving group, followed by migration of the double bond. Interestingly, under the present conditions the reaction exclusively led to the spiroazetidinone 7, probably by way of a regio-and diastereospecific S N 1 substitution (Scheme 4).…”
mentioning
confidence: 98%
“…Baran's approach to synthesise chartelline started from a simple -amino ester 88, which was transformed into a complex amide 89 through a number of steps. 49 The bromination of the latter amide 89 with N-bromosuccinimide, followed by intramolecular cyclisation of the resulting-bromo amide 90, led to the formation of spiro-fused 2-azetidinone 91 (Scheme 29).…”
Section: Cyclisation Reactionsmentioning
confidence: 99%
“…[1][2][3] A related bryozoan Securiflustra securifrons also produces the securines and securamines, 4,5 and they are plausible biogenetic precursors to the chartellines. It was reported that solutions of securine B 1 in DMSO-d 6 converted into securamine B 2, presumably via 1a , Scheme 1. 4 Redissolving 2 in CDCl 3 converted 2 back into 1.…”
mentioning
confidence: 99%
“…The transformation of 1c into 3 can be written as a [1,5]-shift and is a key step in the recently reported biogenetically inspired strategy for the synthesis of 3 by Baran and Shenvi. 6,7 Several other groups have reported on synthetic approaches to chartelline C 6,[8][9][10][11] as well as related alkaloids. 12,13 Our plan was also based on the supposition that the spiro-β-lactam in 3 could arise from a late stage oxidative cyclization of a suitable macrolactam.…”
mentioning
confidence: 99%
See 1 more Smart Citation